La carretera y la ciudad - Munford, Lewis (Revista de Urbanismo, 2005)
Se discute en 1958, el despliegue de las carreteras en los U.S.A., concluyendo que no se tendrá una forma eficiente para el sistema de transporte urbano hasta que se alcance una estructura permanente y mejor para las ciudades. Para lograr el patrón total necesario no sólo debe haber un planeamiento efectivo de la ciudad y de la región antes de que las nuevas rutas o servicios se planifiquen, sino que también se requiere un sistema adecuado de gobierno urbano federado en una escala regional. Abstract The Highway and the City. On the discussion about the development of the highway system in the U.S.A., in 1958, it was concluded that to obtain an efficient system of urban transportation it is necessary to reach a better definition of the structure of the cities. To achieve this goal there has to be an effective plan for the city and region before the new routes and services are placed. But also, it is fundamental that there is a proper federal city government system at a regional level capable to enforce the plan.